Bioethics education on deliberation - a view of a novel: Blue Gold, by Clive Cussler - Magalhães, Susana (2010)
Bioethics education on deliberation - a view of a novel: Blue Gold, by Clive Cussler (Article presented at the conference Bioethics Education: Contents, Methods, Trends, Zefat, Israel, May 2-5, 2010) Authors: Susana Magalhães* (researcher), Joana Araújo (researcher), Ana Sofia Carvalho (Head of the Institute of Bioethics) Research Centre of Bioethics, Institute of Bioethics, Portuguese Catholic University Bioethics education on deliberation - a view of a novel: Blue Gold, by Clive Cussler Since the focus of Bioethics is the bridge between Humanities and the Life Sciences and bearing in mind that this bridge is often difficult to build, those who believe that this dialogue is important in our days should promote it through Education. By educating in Bioethics it is possible to improve the participation of the citizens in debates on the ethical issues raised by new technologies and scientific research. It is our conviction that literary texts are laboratories of ethical judgment, where the ethical questions concerning specific scientific/technological issues are addressed in an imaginary world. Therefore our purpose is to present a framework for ethical deliberation through the use of literature. Fiction allows us to “practise” ethical decision making, by focusing on the particular cases of the characters of the story and by checking how the principles / theories working at the background apply to the narrated cases.